Custo total de uso e propriedade: estudo da aplicação em compras de insumos de produção - Sousa, Luana Martins Guimarães (2020)
Total Cost of Ownership (TCO) is a Strategic Cost Management (SCM) tool for comprehending all of the costs related to the purchase of specific goods, from acquisition to disposal. Nonetheless, few studies are concerned with the use of TCO in input acquisition, as TCO role is usually highlighted in the acquisition of capital goods. Because of it, this research aimed at identifying the main features of the use of TCO to the acquisition process of production inputs. To this purpose, a dyadic approach, single-case study was conducted on an agroindustry purchasing company and on one of its direct suppliers. Based on the Transaction Cost Economics (TCE), the use of TCO was analyzed during the purchase of three strategic inputs required to the production of soybean oil, namely lye, pre-format, and cardboard box. Data were collected in semi-structured interviews, document analysis and direct observation, and then were submitted to Content Analysis. The results showed that the purchasing company applies TCO to those inputs regarded as strategic, as long as the company maintains a close relationship with its own suppliers. Regarding inputs specifically, TCO is mainly used to renegotiate prices with suppliers and manage costs. Moreover, in the purchasing company’s TCO models for purchasing inputs, there are cost drivers and costs which were common to all inputs. However some costs are specific to each purchase. In such models, qualitative factors are not monetarily assessed, but are taken into account in acquiring and negotiating inputs. Another finding relates to the benefits from the purchasing company TCO use, such as reduction in costs, improvement in the relationship with suppliers, input buyers specialization in their own buying category, and better management and perception of the costs related to the inputs. In addition, suppliers’ TCO role is to provide information about costs and to propose, along with the purchasing company, strategies and innovation that reduce costs and improve input and production quality. For this reason, long-term contracts, investments on specific assets and transactions frequency reduce the risk of opportunism and the uncertainty in the relationship, according to the TCE, and support sharing in-depth information as well. Therefore, TCO is used along with both the Open Book Accounting (OBA), since supplier provides TCO analysis with information mainly about costs; and the Interorganizational Cost Management (IOCM), since the purchasing company, along with direct suppliers, seeks alternatives to properly manage costs and to reduce input TCO. In conclusion, TCO is an important tool for knowing the total cost of inputs; some aspects, however, such as the development of close relationship and the sharing of in-depth information mainly about costs, must be taken into account for its effective use, as evidenced by the case study.